2017
DOI: 10.3390/s17102413
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Lightning and Wildfire Hazard by Land Properties and Cloud to Ground Lightning Data with Association Rule Mining in Alberta, Canada

Abstract: Hotspot analysis was implemented to find regions in the province of Alberta (Canada) with high frequency Cloud to Ground (CG) lightning strikes clustered together. Generally, hotspot regions are located in the central, central east, and south central regions of the study region. About 94% of annual lightning occurred during warm months (June to August) and the daily lightning frequency was influenced by the diurnal heating cycle. The association rule mining technique was used to investigate frequent CG lightni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…These variations might be related to one or more of the following reasons. (i) The existing differences in subregion-specific landscape properties, in particular those related to climate, geology, topography, and vegetation [29], could affect the spatial and temporal patterns of lightning strikes [9]. (ii) It is known that the randomness of lightning strike locations highly depends on atmospheric conditions [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These variations might be related to one or more of the following reasons. (i) The existing differences in subregion-specific landscape properties, in particular those related to climate, geology, topography, and vegetation [29], could affect the spatial and temporal patterns of lightning strikes [9]. (ii) It is known that the randomness of lightning strike locations highly depends on atmospheric conditions [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Overlaying the observed lightning-caused fires during the same time period on the derived fire risk map revealed that~69% of the fires fell under the top three classes, i.e., relatively high, high, and extremely high. In addition, over Alberta, Canada, Cha et al [9] analyzed the spatial and temporal patterns of lightning strikes based on landscape properties, i.e., elevation, slope, soil type, and land use to generate a lightning hazard map during the 2010-2014 period. Upon analyzing the lightning strikes' temporal distribution, i.e., occurring hours and months, they identified two thematic maps.…”
Section: Introductionmentioning
confidence: 99%
“…The dominant tree species are Xing'an larch, white birch, and Mongolian pine (Pinus sylvestris var. Mongolia) [50]. This region has an intact community structure with relatively less artificial disturbance.…”
Section: Study Regionmentioning
confidence: 99%
“…ARA methods have been implemented in some wildland fire studies. For example, [30] use ARA to identify hotspots of lightning and wildfires occurrence in Alberta, Canada. Ref.…”
Section: Ara For Resource Categories or Subcategoriesmentioning
confidence: 99%